Substrate Profiling of the Cobalt Nitrile Hydratase from Rhodococcus rhodochrous ATCC BAA 870 - Adelaide R. Mashweu; Varsha P. Chhiba-Govindjee; Moira L. Bode; Dean Brady (Molecules, 2020)
The aromatic substrate profile of the cobalt nitrile hydratase from Rhodococcus rhodochrous ATCC BAA 870 was evaluated against a wide range of nitrile containing compounds (>60). To determine the substrate limits of this enzyme, compounds ranging in size from small (90 Da) to large (325 Da) were evaluated. Larger compounds included those with a bi-aryl axis, prepared by the Suzuki coupling reaction, Morita−Baylis−Hillman adducts, heteroatom-linked diarylpyridines prepared by Buchwald−Hartwig cross-coupling reactions and imidazo[1,2-a]pyridines prepared by the Groebke−Blackburn−Bienaymé multicomponent reaction. The enzyme active site was moderately accommodating, accepting almost all of the small aromatic nitriles, the diarylpyridines and most of the bi-aryl compounds and Morita−Baylis−Hillman products but not the Groebke−Blackburn−Bienaymé products. Nitrile conversion was influenced by steric hindrance around the cyano group, the presence of electron donating groups (e.g., methoxy) on the aromatic ring, and the overall size of the compound.